Pengembangan Aplikasi Augmented Reality sebagai Media Pembelajaran Materi Bangun Ruang Sisi Datar Kelas VIII SMP Negeri 13 Mataram - Lalu Riki Gita Sukma; Sudi Prayitno; Baidowi Baidowi; Amrullah Amrullah (PALAPA, 2022)
This development research aims to develop applications based on augmented reality as a medium of learning material build flat side space and meet the criteria of valid, practical, and effective to use. This type of research is research and development (R&D) by adopting the 4D model, namely define, design, develop, and disseminate. At the stage of development conducted a trial by using one group Pretest-Posttest Design with research subjects as many as 25 students of Class VIII SMP Negeri 13 Mataram were selected using a simple random sampling technique. Data collection is done using test instruments’ validity, practicality, and effectiveness. The data obtained from this study are: (1) validity test based on the assessment of 3 expert validators get an average result of 4.5933 with a very valid Category; (2) practicality test based on the assessment of students get an average percentage of 92.27% of all aspects assessed; (3) the effectiveness test was conducted by analyzing the results of pretest and posttest with paired t-test Test and there was an increase in student learning outcomes, but the results of the N-gain Test obtained a percentage of 48.9429 with less effective categories. The level of effectiveness obtained by the media is due to some shortcomings of the developed media. Based on these results, it can be concluded that the media developed is very valid and very practical to be used in learning, but still less effective in improving the learning outcomes of learners, so the media needs to be developed further.